PENGARUH DISIPLIN KERJA, PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KINERJA KARYAWAN HOTEL DI KOTA PALOPO - Rahmawati Hasni; Edi Maszudi; Samsinar Samsinar (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to identify and analyse the effects of work discipline, career development, and compensation on the performance of hotel employees in Palopo City in 2025. Methods: In this study, the research is quantitative, with a survey administered via questionnaire distribution. The population in this study were hotel employees in Palopo City. The sampling used simple random sampling. The sample size in this study is 65 employees. The data used in this study are primary data collected via a questionnaire. The data analysis method in this study used multiple linear regression with the SPSS (Statistical Product and Service Solutions) application. Results: Based on the study, work discipline does not significantly affect employee performance, despite it being a basic norm. Career development has a positive and significant effect, partially through training and promotions that encourage motivation. Compensation has a positive and very significant effect, as a dominant factor that spurs productivity through salaries and benefits on the performance of hotel employees in Palopo City. Keywords: Career Development, Compensation and Employee Performance, Work Discipline